2020
DOI: 10.1080/19490976.2020.1736457
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of LRP6-CRISPR on prevention of alcohol-related liver injury surpassed fecal microbiota transplant in a rat model

Abstract: Alcohol intake can modify gut microbiota composition, increase gut permeability, and promote liver fibrogenesis. LRP6 is a signal transmembrane protein and a co-receptor for the canonical Wnt signaling pathway. This study compared the curative effect of LRP6-CRISPR on alcohol-related liver injury with that of traditional fecal microbiota transplant (FMT) and investigated the alteration of the gut microbiome following the treatment. A rat model of alcohol-related liver injury was established and injected with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 52 publications
5
21
0
Order By: Relevance
“…Multiple S24-7 phylotypes were associated with all the MCS and CCl 4 groups, suggesting different S24-7 phylotypes could play different roles in each of the six groups. This is consistent with the previous findings, which hold different views on the roles of Bacteroidales S24-7 in the gut microbiota [ 35 , 36 ]. Multiple OTUs assigned to Clostridiales were associated with M48, among which OTU375_ Clostridiales was most associated with M48.…”
Section: Discussionsupporting
confidence: 93%
“…Multiple S24-7 phylotypes were associated with all the MCS and CCl 4 groups, suggesting different S24-7 phylotypes could play different roles in each of the six groups. This is consistent with the previous findings, which hold different views on the roles of Bacteroidales S24-7 in the gut microbiota [ 35 , 36 ]. Multiple OTUs assigned to Clostridiales were associated with M48, among which OTU375_ Clostridiales was most associated with M48.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we observed that alcohol consumption increased Prevotella and Parasutterella and decreased Clostridium , Turcibacter and Romboutsia , which is in line with the previous reports [ 46 , 47 , 48 , 49 ]. Moreover, alcohol consumption also increased the abundance of some of the gram-negative bacteria (i.e, Porphyromonadaceae and Alloprevotella ).…”
Section: Discussionsupporting
confidence: 93%
“…Romboutsia can metabolize carbohydrates, synthesize amino acids and vitamins, and are sensitive to bile acids ( Gerritsen et al, 2017 ). Some studies suggest that Romboutsia may be linked to obesity ( Hu et al, 2019 ) and liver injury ( Yu et al, 2020 ). Furthermore, a large number of studies have directly or indirectly proved that Romboutsia and Lactobacilli show opposing trends in relative abundance ( Chen et al, 2019 ; Lee et al, 2019 ; Qiao et al, 2019 ; Xu S. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%